Exploring the consequences of foreign aid on economic performance in sub-Saharan Africa - Sawyerr, David Toluwani (My University, 2022)
Economic growth is embedded in the DNA of governments with the objective of creating shared prosperity between the state and society. Fundamental principles of political economics dictate that capital is an essential aspect of creating economic growth. In Sub-Saharan Africa (SSA), capital has often been in the form of foreign aid provided by donors. These donors often attach governance conditions to their aid, to bolster the effectiveness of aid which, it is believed, will promote economic growth and development. One of the governance conditions is the participation of civil society in public discourse and the legislative process between the state and society. To facilitate the vertical accountability between the state and society, Civil Society Organisations (CSOs) were established globally, and particularly, in Sub-Saharan Africa, to represent the interests of society, as governments enact policies that should enable economic growth. This study investigates the conditioning effect of CSO consultation on the impact of foreign aid on economic growth. Furthermore, data from 41 SSA countries, between 1960 and 2018, for which data was available, are utilised. The main purpose of the study was to examine CSO’s effect on the nexus between aid and growth as the nexus itself has been well examined. Some studies have also investigated CSOs but this study presents novel arguments on the role of CSOs in the aid-growth discourse. The study used time series cross sectional analysis to determine the conditioning effect of CSO consultation on aid and economic growth by utilising over 1,700 observations. Contrary to general assumption by donors and policymakers, the results of the econometric analysis show that while foreign aid statistically contributes positively to economic growth in SSA, the conditioning effects of CSO consultation yielded a negative relationship between foreign aid and economic growth. The results were largely consistent with varying timeframes and country classifications.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in 50% fulfilment of the requirements for the degree of Master of Management (in the field of Governance).
Keywords: UCTD; Foreign aid; Civil society organisations; Economic growth; GDP; Political factors; Econometric model; SDG-8: Decent work and economic growth